2016
DOI: 10.3390/e18020062
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation and Corrosion Properties of High Entropy Superalloys

Abstract: Abstract:The present work investigates the high temperature oxidation and corrosion behaviour of high entropy superalloys (HESA). A high content of various solutes in HESA leads to formation of complex oxides, however the Cr and Al activities of HESA are sufficient to promote protective chromia or alumina formation on the surface. By comparing the oxidation and corrosion resistances of a Ni-based superalloy-CM247LC, Al 2 O 3 -forming HESA can possess comparable oxidation resistance at 1100˝C, and Cr 2 O 3 -for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 45 publications
(45 reference statements)
4
42
1
Order By: Relevance
“…The materials should exhibit good mechanical strength and surface stability at elevated temperatures . Therefore, in our previous study, face‐centered cubic (FCC) high entropy Ni‐based alloys with L1 2 γ′ precipitates were developed, as the strengthening mechanism of superalloys. The uniformly distributed γ′ can be coherent with the FCC γ matrix and remain stable till high temperatures to impart strengthening .…”
Section: Introductionmentioning
confidence: 99%
“…The materials should exhibit good mechanical strength and surface stability at elevated temperatures . Therefore, in our previous study, face‐centered cubic (FCC) high entropy Ni‐based alloys with L1 2 γ′ precipitates were developed, as the strengthening mechanism of superalloys. The uniformly distributed γ′ can be coherent with the FCC γ matrix and remain stable till high temperatures to impart strengthening .…”
Section: Introductionmentioning
confidence: 99%
“…Elemental map analysis of Ni at the interface of base metal–wustite (zone A in Figure a) showed that this zone is richer in Ni than the base metal. This enrichment, as shown in Figure a, is probably because that Ni is more noble than iron and therefore it accumulates at the oxide–metal interface . As will be shown later, the diffusion of Ni in iron is very slow and as a result, it could not diffuse back rapidly to iron and will concentrate at the oxide–metal interface.…”
Section: Resultsmentioning
confidence: 89%
“…Tsao et al [223] investigated the high-temperature oxidation and corrosion properties of high-entropy superalloys based on Al-Ti-Cr-Fe-Co-Ni system and compared their properties with CM247LC -Ni-base superalloy. The oxidation tests were performed in the temperature range of 900-1100 C for the duration of 5-200 h. They studied the corrosion behavior by performing the salt-coated and crucible tests.…”
Section: High-temperature Oxidation and Hot Corrosion Resistancementioning
confidence: 99%